ANALYSIS OF HEPATITIS B TRANSMISSION POTENTIAL IN THE FAMILY OF PATIENTS USING HBsAg RAPID SCREENING TEST - Dr Laksmyn Kadir M.Kes; I Made Ari Setiawan (International Journal of Health Science & Medical Research, 2022)
Hepatitis B virus (HBV) is the cause of liver disease, found in human body fluids such as saliva, vaginal fluids, semen, and blood. HBV can be transmitted through sex, sharing syringes, baby-mother intercourse, and touching involving bodily fluids. The novelty of this study is that it analyzes the potential for hepatitis B transmission using the HBsAg Rapid Screening Test. The purpose of this study was to analyze the potential for transmission of hepatitis B to the families of patients with patients. This research uses a quantitative method with a descriptive type. The examination used was the immunochromatographic method on venous blood samples of 22 families. The results of the study showed that there were households where one member was detected as HBsAg positive, and 18 other households were HBsAg negative. Transmission of Hepatitis B Virus (HBV) in the family is as much as 9.09% with the family status of parents and children. It is suspected that children who contracted HBV were the result of close contact that lasted for quite a long time, which allowed HBV particles to move. Moreover, the child lives in the same house with the mother, who takes care of him. The conclusion of this study is that the patient's family who has close contact with hepatitis B sufferers can be infected with hepatitis B.Keywords: Virus; Hepatitis B; Immunochoromatography.